A review on bioactive glass and lumbosacral fusion surgery - Lehtimäki, Jesse (My University, 2025)
The objectives of this literature review are to explore composition, properties, and clinical applications of bioactive glass (BAGs), with specific a focus on lumbosacral fusion. Additionally, this review examines bioactive glass S53P4 in lumbar fusion surgeries. The final section provides a summary of our upcoming study on clinical safety and efficacy of BonAlive S53P4 in lumbosacral fusion surgery. Bioactive glass is an inorganic biomaterial developed in 1969. Since then, extensive research has led to new compositions and improved bioactivity. The primary component of bioactive glass is silicate, with additional elements such as calcium, sodium, magnesium, and phosphorus. Bioactive glasses are characterized by their osteoconductive, osteoinductive and angiogenic properties. Some bioactive glasses also possess antimicrobial properties. They are used in dentistry, orthopedics, and infection treatment. Furthermore, they are biocompatible and bioresorbable, allowing them to integrate directly with host tissue and degrade over time. In spinal fusion surgery, bioactive glasses are used either alone or as bone graft extenders in combination with autologous bone to promote bone growth between vertebrae. While autologous bone graft remains the gold standard for spinal fusion, bioactive glasses have produced comparable outcomes when used as a bone graft extender. They are particularly advantageous in minimally invasive surgery and revision surgery, where the amount of available autologous bone may be limited. Lumbosacral fusion surgery is often the preferred procedure in cases where the spine is unstable. Instability can be present before operation or arise from a larger amount of bone material removed during the operation. The most common technique for lumbar fusion surgery is posterolateral fusion (PLF), which typically involves internal fixation using pedicle screws and bilateral rods. Lastly, bone graft material is placed on top of the transverse processes to facilitate bone fusion. Although bioactive glasses have significant potential in spinal fusion surgery, current evidence suggests that they do not yet achieve similar fusion rates as autologous bone. Additionally, bioactive glasses are inherently brittle, making them less suitable for bone graft substitutes in load-bearing sites such as the lower lumbar spine. In the future, more extensive research should be conducted to improve the mechanical properties of bioactive glasses and conduct long-term clinical studies and randomized controlled trials (RCTs) to better understand their efficacy and safety in spinal fusion procedures. Our upcoming research article investigates the clinical efficacy and safety of the bioactive glass BonAlive® S53P4 in lumbosacral fusion surgery.
Keywords: Bioactive glass, Lumbosacral fusion surgery, S53P4, spinal surgery, bone graft